PHYSICOCHEMICAL DYNAMICS OF COMPONENT PRECIPITATION FROM MAGMATIC GAS PHASE ABOVE MANTLE SOURCES OF BASIC MELT - Sharapov V.N.; Akimtsev V.A.; Ashchepkov I.V.; Cherepanov A.N. (My University, 2004)
The precipitation of a set of minerals by condensation of magmatic fluid is an immanent specific feature of subaerial and submarine basic magmatic systems evolving at various depths. The description of temperature zoning of equilibrium condensation of magmatic fluid at a temperature above the existence of droplike liquid water solution is the subject of this paper. To estimate the variation of PT parameters of fluid filtration above a mantle source of boiling basic melt, we solved the problem of nonstationary dynamics of the multilayer lithosphere heating. (1) Thickness of the upper and lower Earth's crusts and upper mantle was accepted as 0-10, 10-30, and 30-40 km, respectively; (2) porosity kr and permeability Kr decrease downward the litosphere according to the law: kr = a - b(Z/H m, where m = 1/3-2) and Kr,h = 10 -12m3/(1 - Kro)2; (3) the magmatic chamber occurs at a depth of 40 km, and <1% of the gas mixture is released at the upper front of the stationary solidus. It has been found that at Kro = 10-16-10 -17 m2 a quasiadiabatic temperature profile is formed over 0.3-1.0 Ma. The physical chemistry of mineral precipitation from the gas phase was modeled with a Selector-S program complex using a scheme of flow reactors with a uniform time step: the outer gas reservoir → basic rock → fractured mantle rock 1 → fractured mantle rock 2 → "....-n(8-18)" → receiver of fluid. The computation was carried out for websterite mantle, alkali basalt, and gas phase of O-C-H-N-Cl-F-S composition; initial pressure Po of gas mixture in the reservoir is 10-20 kbar, To = 1100-1200°C; the final temperature Tk at the outlet from the filtration region is 750-400°C, and the final pressure Pk = 1.0-0.5 kbar. The numerical experiments simulate, in general outlines, the composition of condensates deduced from samples of deep xenoliths: olivine, orthopyroxene, clinopyroxene, K-feldspar, spinel, magnetite, sulfides, quartz, and salts. Various realizations are suggested for the dynamic transfer and precipitation of major components by magmatic fluids: (1) formation of ephemeral zones of precipitation and dissolution with further complete disappearance is inherent to some minerals (K-feldspar); (2) an initial nonstationary region and quasistationary zone of precipitation with increasing height of precipitation wave are typical of other compounds (olivine); and (3) minerals with a stationary precipitation region are also known (magnetite). A quasistationary state of the system for various fluid compositions is established after 45-50 relative temporal steps.